44 In-hospital outcomes for patients undergoing percutaneous or surgical coronary revascularization and aortic stenosis intervention: a propensity score matched analysis from a national health database. (6th October 2022) - McInerney, A; García Márquez, M; Luis Bernal, J; Fernández-Pérez, C; Tirado-Conte, G; Jimenez-Quevedo, P; Fernandez-Ortiz, A; Nuñez-Gil, I; Gonzalo, N; del Prado, N; Escaned, J; Elola, J; et al.
Abstract : Introduction and Objectives: Concomitant coronary artery disease is prevalent among patients with symptomatic severe aortic stenosis. We aimed to investigate the periprocedural outcomes among patients undergoing transcatheter aortic valve replacement with percutaneous revascularization (TAVR/PCI) versus surgical aortic valve replacement with concomitant coronary artery bypass grafting (SAVR/CABG). Methods: Using discharge data from the Spanish National Health Care system, 6194 patients were identified (5217 SAVR/CABG and 977 TAVR/PCI) between 2016 and 2019. A propensity score matched analysis resulted in 774 pairs of patients. The primary outcome was in-hospital mortality. Results: In-hospital mortality was more common in the matched SAVR/CABG group (3.4 %versus 9.4%, p<0.001) as was acute kidney injury (4.3% versus 16.0% p<0.001) periprocedural stroke (0.9% versus 2.2% p=0.004), blood transfusion (9.6% versus 21.1%, p<0.001) and hospital acquired pneumonia (0.1% versus 1.7%, p=0.001). Permanent pacemaker (PPM) implantation was higher in TAVR/PCI patients (12.0% versus 5.7%, p<0.001). Lower volume centres (<130 procedures per year) were associated with higher in-hospital mortality than high volume centres for both TAVR/PCI (3.6% versus 2.9%, p<0.001) and SAVR/CABG (8.3 versus 6.8% P<0.001). Conclusions: This nationwide analysis showed that staged percutaneous revascularization and TAVR was associated with less in-hospital mortality and periprocedural complications except PPM implantation than concomitant SAVR and CABG. Higher volume centres are associated with less in-hospital mortality for both TAVR/PCI and SAVR/CABG and dedicated national high-volume heart centres warrant further investigation.